Bridging the Gap between Theory and Practice in Educational Research - Winkle-Wagner, Rachelle. author. aut Link
XI, 271 p.
Keywords: This book provides new ways of thinking about educational processes, using quantitative and qualitative methodologies. Ultimately, it aims at expanding knowledge itself - altering the centre by allowing the margins to inform it - allowing it to be extended to include those ways of knowing that have historically been unexplored or ignored.